A RESEARCH STUDY ON THE CAUSES OF DIFFERENCES BETWEEN IMAM ABU HANIFA AND HIS DISCIPLES - Raza Muhammad; Dr.Taj ud Din Al-Azhari (Journal of Religion and Society, 2025)
Imam Abu Hanifa (699–767 CE), one of the greatest jurists in Islamic history, laid the foundation of the Hanafi school of thought, which later became one of the four major Sunni legal schools. However, differences of opinion arose between Imam Abu Hanifa and his prominent disciples, such as Imam Abu Yusuf, Imam Muhammad, and Imam Zufar. These variations in jurisprudential rulings were not due to fundamental disagreements but rather stemmed from different methodologies in legal reasoning (ijtihad), interpretations of hadith, and approaches to analogical deduction (qiyas). This research explores the causes of these differences by analyzing historical, methodological, and contextual factors that influenced the juristic decisions of Imam Abu Hanifa and his students. Key factors include variations in sources of legal evidence, the acceptance and rejection of certain hadiths, differences in understanding textual implications, and the influence of local customs and societal conditions. Additionally, this study highlights how such scholarly debates enriched Islamic jurisprudence and contributed to its dynamic and adaptive nature. By delving into classical Hanafi texts and examining scholarly discussions on the subject, this research aims to provide a comprehensive understanding of the reasons behind these differences and their impact on the evolution of Islamic legal thought. Keywords: Imam Abu Hanifa, Hanafi School, Islamic Jurisprudence, Legal Reasoning, Ijtihad, Qiyas, Hadith Interpretation, Disciples, Islamic Law